Evaluation of the aerobic biodegradability of process water produced by hydrothermal carbonization and inhibition effects on the heterotrophic biomass of an activated sludge system. (1st December 2021) - Langone, M.; Sabia, G.; Petta, L.; Zanetti, L.; Leoni, P.; Basso, D.
Abstract: In this work, the aerobic biodegradability of the process water (PW) produced by hydrothermal carbonization (HTC) of dewatered anaerobic digested sludge and the toxicity assessment in regard to the heterotrophic activated biomass of a conventional activated sludge systems, are described. Such assessments are not yet reported in other scientific papers, so this paper seeks to contribute to the increase of knowledge regarding the valorization of the HTC process applied in a wastewater treatment plant (WWTP). For such purpose, two different respirometric techniques were applied - multi-OUR respirometry and manometric respirometry. PW resulted highly biodegradable: 83% of total COD was biodegradable, with a 58% of readily biodegradable (rbCOD) fraction. The BOD5 /COD ratio was 0.42. Further, it was characterized by a high concentration of volatile fatty acids (VFAs) (i.e. 2031 mg/L), of which the major constituent was acetic acid (i.e. 80%), an easily degradable intermediate of many biological processes. Both the respirometric techniques showed that the assessed PW, after being diluted accordingly with the WWTP real operational conditions, did not imply short-term toxic effects on the activated sludge, neither using fresh biomass nor keeping the same one. According to these results, the recirculation of PW at the water line of WWTPs represents a promising approach not affected by specific toxicity issues, especially when the HTC process is integrated into a WWTP scheme. Graphical abstract: Image 1 Highlights: Recirculation of HTC process water at the water line of WWTP is a promising approach. Respirometry was used for short-term toxicity evaluation on heterotrophic bacteria. No evidence of toxic effect was found at dilution factor higher than 1:666.